Soil cover and planting seasons in iceberg lettuce grow under organic farming - Forlan, Pablo Vargas [UNESP] (2014)
In Brazil, the lettuce is a leafy vegetable of greatest economic importance. Among the varieties of this vegetable, the iceberg has been highlighting as it gets an expressive position in the consumer market, mainly for fast food chains. As the competitive market grows, the producers search for techniques that promote a differentiated production and trading process through the good appearance and quality of their products. In this way, the organic products have a great potential as the lettuce has an increasing acceptance in the in natura market, being consumed raw in salad. The soil cover has increasingly been used in lettuce growing as it brings some advantages to the cultivation as humidity and temperature maintenance. However, there is little information about the changes made by different soil cover types over the organic lettuce grow. Therefore, the actual research has as goal to evaluate different types of soil cover in different planting seasons. The trial has been performed at University of Minas Gerais State/Foundation of Higher Education in Passos (20 degrees 43' 13 '' South, 46 degrees 36' 36 '' West). The experimental design was randomized blocks for each planting season, with four replications. The treatments were based in the soil covers of: black plastic, double sided plastic (black bottom and white top), coffee rusk, rice straw, sawdust, chopped napier grass, white fabric, and a control (without soil cover). The planting season were: June 1st and July 13th, 2009 and the used cultivar was Lucy Brown. The lettuce harvesting was performed when the plants reached the maximum plant growth and the evaluated factors were head diameter, plant height (biggest leaf length), total and marketable fresh mass and commercial production index. By the means of each evaluated factor, the F test was applied and comparisons made by Tukey test at 5% probability. An additional study was the joint analysis, which was performed to identify the possible interaction among the studied factors (soil cover and planting season). The covers of black (419 g plant(-1)), double sided plastic (351 g plant(-1)) and coffee rusk (406 g plant(-1)) increased the production of the iceberg lettuce.